Connexins in the Central Nervous System: Physiological Traits and Neuroprotective Targets - Vicario, Nunzio; Zappalà, Agata; Calabrese, Giovanna; Gulino, Rosario; Parenti, Carmela; Gulisano, Massimo; Parenti, Rosalba (Frontiers in Physiology, 2017)
Cell-to-cell interaction and cell-to-extracellular environment communication are emerging as new therapeutic targets in neurodegenerative disorders. Dynamic expression of connexins leads to distinctive hemichannels and gap junctions, characterized by cell-specific conduction, exchange of stimuli or metabolites and particular channel functions. Herein, we briefly reviewed classical physiological traits and functions of connexins, hemichannels and gap junctions, in order to discuss the controversial role of these proteins and their mediated interactions during neuroprotection, with a particular focus on Cx43-based channels. We pointed out the contribution of connexins in neural cells populations during neurodegenerative processes to explore potential neuroprotective therapeutic applications.